A REVIEW OF LEAN APPLICATION IN MANUFACTURING ENVIRONMENT: DEFINITIONS AND TERMINOLOGIES (Journal of Technology and Operations Management, 2019)
This article is a review of definitions and terminologies used in existing literatures related to application of Lean System in manufacturing environment. The article is made to provide clear insight and comparisons on various terms used in contemporary academic journals, books and published theses on the subject of Lean System. This review realizes that the term Lean Manufacturing was more popular among Malaysian and Asian countries, while Lean Production was mostly used by American scholars. From this review, readers also might learn that Lean System and Toyota Production System are not really the same system due to a missing principle. The present review is concluded with visual explanation regarding several major jargons in Lean System.